FOOT AND MOUTH DISEA SE EPIZOOTOLOGICAL SURVEILLANCE IN WILD ANIMAL POPULATION IN ZABAYKALSKY KRAI (RUSSIA) AS EXAMPLE - V. V. Nikiforov; T. V. Vadopalas; D. A. Lozovoy; E. V. Kiriltsov; S. P. Semakina (Ветеринария сегодня)
Wild animals can be a potential source of livestock infectious diseases. This problem is particularly relevant in the areas of distant-pasture cattle rearing where wild and domestic animals often contact on pastures and near watering places. Therefore, dzerens (or Mongolian gazelles) migrating from the border areas of Mongolia and China to the Russian Federation can be the source of infection in wildlife. In this connection, the determination of the role of wild dzeren gazelles in the spread of foot and mouth disease is an urgent task. The paper presents information collection and epizootological data analysis with regard to dzeren migration from Mongolia to the the Zabaykalsky Krai (the Russian Federation) for the period of 1992–2018. The FMD epidemic situation in the the Zabaykalsky Krai (the Russian Federation), Mongolia, and China in 2005–2018 is given. FMD virus serotypes that caused outbreaks in the the Zabaykalsky Krai of the Russian Federation from 2006 to 2018 were correlated with the serotypes identified in Mongolia. Biomaterial samples from 20 dzerens were tested in the FGBI “ARRIAH” Laboratory and Diagnosis Center. The laboratory testing results have confirmed FMD virus circulation in the population of dzerens migrating to the border areas of the Russian Federation from the adjacent areas of Mongolia. The potential threat of the FMD virus introduction into the territory of the Zabaykalsky Krai of the Russian Federation by wild animals is specified. The necessity of arranging FMD surveillance system in the population of susceptible wild migratory animals is also justified.